Thinking Transindividuality along the Spinoza-Marx Encounter: A Conversation - Bram Wiggers; Jason Read (Krisis, 2022)
Ever since the publication of Read’s The Politics of Transindividuality (2015), the academic interest in transindividuality has steadily mounted. In this conversation, Bram Wiggers and Jason Read discuss the current state of affairs around the concept of transindividuality. The conversation begins with a definition of transindividuality and discusses what sets the term apart from other philosophies of social individuation. Having defined the concept of transindividuality, the conversation then engages with the question of how transindividuality can be adopted as a means of social-political critique. First, Bram and Jason discuss how transindividuality is evoked but not explicitly mentioned in the social-political critiques of Spinoza and Marx. Secondly, the conversation takes up the social-political critiques of Paolo Virno and Bernard Stiegler who make explicit use of transindividuality. Central to the later parts of the conversation is the complicated interrelation between the political and economic domains of individuation, as well as the tendency of collective modes of representation to be effaced and obscured by (neoliberal) individualism and the post-Fordist conditions of labor. Overall, the conversation highlights the relevance of transindividuality for social-political philosophical critique.